Displacement Pattern of Anterior and Posterior Column Fragments in Both-Column Acetabular Fractures: A 3D Reconstruction-Based Study. (20th October 2022) - Ye, Pengyu; Guo, Junfei; Wang, Zhongzheng; Tian, Siyu; Zhao, Kuo; Yin, Yingchao; Hou, Zhiyong; Zhang, Yingze
Abstract : Background . Few studies have been conducted to examine the displacement characteristics of both-column acetabular fractures (BCAFs). The goal of this study was to investigate the displacement pattern of anterior column (AC) and posterior column (PC) fragments in BCAFs using 3D virtual software. Materials and Methods . BCAFs were retrospectively reviewed, and 81 patients were enrolled. Computed tomography (CT) images were imported into Mimics software. A 3D model of each pelvis was generated. Four marked points and the rotation angle of each of the injured ACs and PCs were identified. The fracture fragments were reduced virtually using the software, and the change in coordinates of the marked points after reduction was recorded while the rotation angle was measured. The measurements of positional and directional displacement were analysed using the Mann–Whitney U test and the binomial test, respectively. Results . There was a propensity for AC fragments to shift superomedially and to rotate externally (p < 0.001 ). Additionally, the posteroinferior fracture area of AC fragments showed the greatest displacement (p < 0.05 ). PC fragments moved superomedially (p < 0.001 ) and moved more at the proximal end than the distal end (p < 0.001 ). PC displacement was always accompanied by internal rotation (p < 0.001 ). Greater AC displacement was observed in the fracture area further away from the acetabulum (p < 0.05 ). Greater rotation was observed for the AC than the PC (p < 0.001 ). Conclusion . After a BCAF occurs, there are regular patterns regarding the direction and distance of AC and PC fragment displacement. Information on these patterns may provide insight into the injury mechanism and fracture morphology and facilitate surgical decision-making for orthopaedic trauma surgeons.